2017
DOI: 10.1016/j.rboe.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Subchondroplasty for treating bone marrow lesions in the knee – initial experience

Abstract: ObjectiveTo evaluate the use of subchondroplasty in the treatment of bone marrow lesions in an initial series of five cases.MethodsThe study included patients aged between 40 and 75 years old, with pain in the knee for at least six months, associated with high-signal MRI lesion on T2 sequences, on the tibia or femur. Patients were assessed using the visual analog pain scale and the KOOS score, one week before surgery and one, three, six, 12, and 24 weeks after the procedure. Subchondroplasty was performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
97
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(103 citation statements)
references
References 24 publications
(27 reference statements)
3
97
0
3
Order By: Relevance
“…However, it is important to note that SCP‐treated knees showed relatively more functional impairment than non‐treated knees at the two early assessment time points. Similar findings have been reported in some patients receiving SCP injections in the knee who reported mild to moderate pain in the initial time period after treatment . This initial impairment may have been exacerbated in dogs in the present study due to the perceived overfill and extravasation of the injectate, and attention to this factor is important for further preclinical study and clinical application of SCP treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, it is important to note that SCP‐treated knees showed relatively more functional impairment than non‐treated knees at the two early assessment time points. Similar findings have been reported in some patients receiving SCP injections in the knee who reported mild to moderate pain in the initial time period after treatment . This initial impairment may have been exacerbated in dogs in the present study due to the perceived overfill and extravasation of the injectate, and attention to this factor is important for further preclinical study and clinical application of SCP treatment.…”
Section: Discussionsupporting
confidence: 89%
“…The beneficial outcomes associated with SCP treatment noted in the present study are similar to clinical outcomes in 66 patients treated with SCP for BMLs by Cohen et al who reported significantly less pain and better function based on visual analog scale (VAS) and International Knee Documentation Committee (IKDC) assessments, respectively, through 2 years after treatment. Similarly, Bonadio et al demonstrated significantly improved outcomes for pain and function assessed by VAS and IKDC, respectively, in a series of five patients who underwent SCP for BMLs and were followed through 6 months after treatment. In another study evaluating the effect of SCP on outcomes in patients with knee BMLs, Chatterjee et al reported significant improvements in Knee Injury and Osteoarthritis Outcome Scores (KOOS) and Tegner‐Lysholm Knee Scoring in a non‐matched cohort of 22 patients with advanced knee OA who underwent SCP and were followed through 6 months after treatment.…”
Section: Discussionmentioning
confidence: 75%
“…Beneficial clinical outcomes associated with SCP treatment for BMLs including significantly less pain and improved functional scores through 2 years after treatment have been reported. 19,24 There are currently no studies evaluating PRP or BMC treatment of BMLs. However, there are studies that have looked at intraosseous (IO) injection of PRP in patients with more advanced knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…While SCP has reported clinical benefits in treating subchondral bone pathology and can be considered an orthobiologic, it has been associated with significant morbidity when used at higher volumes, and alone, does not fully address the current gap in treatment . As such, combination therapy to include other orthobiologics with CaP bone void filler may be beneficial.…”
mentioning
confidence: 99%
See 1 more Smart Citation